The role of teachers in educational leadership at madrasah ibtidaiyah manggarupi gowa - Muhammad Muhaimin; Andi Achruh; Rosdiana; Nidya Nina Ichiana (Balai Diklat Keagamaan Ambon, 2024)
This research aims to investigate the role of teachers in educational leadership. The method employed is qualitative, specifically descriptive, utilizing data sources from the Islamic Schools Headmasters and teachers. Data collection techniques include observation and interviews. Data analysis involves data reduction, data presentation, and sequential conclusion drawing and verification. The findings reveal that: 1) Teachers' understanding of educational leadership influences their roles and interactions at MI Manggarupi. Teachers with a strong understanding tend to be more effective in enhancing learning quality, motivating students, fostering positive relationships, and collaborating with the school. 2) A harmonious relationship between teachers and the Islamic school Headmaster plays a crucial role in the teachers' position within educational leadership. The teachers' leadership position is reinforced through active involvement in decision-making and professional development programs. 3) Teacher involvement in decision-making at Islamic schools reflects their position within educational leadership. The implications of this research are: 1) It is imperative to enhance teachers' understanding of educational leadership. 2) There should be a strengthening of the relationship between teachers and the Islamic school's Headmaster to achieve effective cooperation, thereby ensuring each teacher holds a leadership position. 3) Teachers should be involved in decision-making within the Islamic schools' programs, which can improve trust and motivation among teachers and strengthen their position within educational leadership